Contribution of Academic Self-Concept and Parental Social Support to Learning motivation - Ayunil Ummi; Sufyarma Marsidin; Mudjiran Mudjiran (Universitas Negeri Padang, 2020)
Contribution of academic self-concept and parental social support to learning motivation. This research is motivated by the low student motivation. Academic self-concept and parental social support are thought to have an effect on student motivation. This study aims to describe: (1) academic self-concept, (2) parental social support, (3) student learning motivation, (4) Contribution of academic self-concept to student learning motivation, (5) contribution of parental social support to student learning motivation , and (6) the contribution of academic self-concept and parents' social support together on learning motivation. This research uses a descriptive correlational quantitative method. The study population was students of class X and XI at SMKN 6 Padang, totaling 983 students, a sample of 284 students, who were selected by using cluster random sampling technique. The results of this study indicate that academic self-concept and parental social support together have a significant effect on learning motivation at SMKN 6 Padang by 64.5%. The implications of the results of this study can be used as a needs analysis in making Guidance and Counseling service programs at SMKN 6 Padang.